A lithium metal negative electrode bipolar artificial SEI film and a preparation method and application thereof

CN117175035BActive Publication Date: 2026-11-03BEIJING INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311366444.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2026-11-03
Estimated Expiration
2043-10-20

AI Technical Summary

Technical Problem

Existing artificial SEI films for lithium metal anodes have shortcomings in terms of high ionic conductivity and high ion transference number, resulting in poor lithium dendrite growth and battery cycle stability, which limits their application in lithium secondary batteries.

Method used

A bipolar artificial SEI film for lithium metal anodes was prepared by coating a mixed solution of carbonate, polar polymer, polymer prepolymer, photoinitiator and lithium salt onto the surface of lithium metal and curing it under ultraviolet light. Through the interaction of polar cyano groups and alcohol hydroxyl functional groups, a tightly attached polymer-derived SEI film was formed, which enhanced ionic conductivity and lithium ion migration.

Benefits of technology

The prepared lithium metal anode bipolar artificial SEI film has both high ionic conductivity and high ion transference number, effectively preventing carbonate solvent corrosion, stabilizing the lithium ion deposition process, inhibiting dendrite growth, and improving battery safety and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117175035B_ABST
    Figure CN117175035B_ABST
Patent Text Reader

Abstract

The artificial SEI film has high ionic conductivity and high ionic transference number, contains bipolar functional groups, promotes desolvation of lithium ions, reduces solvent-induced corrosion of the lithium negative electrode, and can also adsorb anions to improve the lithium ion migration efficiency. The artificial SEI film can reduce the concentration polarization of lithium ions, realize uniform deposition of lithium metal ions, and inhibit the generation of lithium metal dendrites. The artificial SEI film is essentially a self-supporting film formed by mixing a polar polymer, a carbonate solvent, a lithium salt, a polymer prepolymer and a photoinitiator, and then curing in situ. The artificial SEI film prepared by the method can effectively protect the lithium metal negative electrode; the preparation process of the method is simple, conventional equipment is used, raw materials are easy to obtain, and the method is safe, pollution-free and suitable for large-scale batch production. When the artificial SEI film is used in a lithium metal battery, it can match high-voltage positive electrode materials and has good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a bipolar artificial SEI film for lithium metal anodes, its preparation method, and its application. The artificial SEI film is used to protect the lithium metal anode material in lithium metal batteries and belongs to the technical field of lithium metal batteries. Background Technology

[0002] Lithium metal has an extremely high theoretical specific capacity (3860 mAh g). -1 With its extremely low redox potential (-3.040V vs. standard hydrogen electrode), it is a high-energy-density lithium metal battery (>500Wh / kg). -1 Lithium metal is the optimal material for the anode. However, due to the high reactivity of lithium metal with commercial carbonate electrolytes, a non-uniform organic / inorganic solid electrolyte interphase (SEI) layer is formed. Regulating the lithium metal anode interface is an effective strategy to suppress lithium metal anode failure, including electrolyte modification and the construction of artificial SEI films. Electrolyte modification mainly involves three methods: using high-concentration electrolytes to regulate the composition of the lithium surface SEI film, using additives to regulate uniform lithium ion deposition, and promoting the formation of a stable SEI film on the lithium metal surface. However, during battery cycling, electrolyte additives and lithium salts are gradually consumed, leading to non-uniform composition and surface structure of the subsequently formed SEI film, which in turn causes non-uniform lithium deposition and the formation of lithium dendrites. Therefore, exploring efficient artificial SEI films with uniform structure, good toughness, high ion conductivity, and surface electronic insulation is of great significance.

[0003] Currently, artificial SEI films can effectively prevent uncontrolled lithium dendrite growth and regulate uniform lithium-ion diffusion. The research group of Professor Huang Yunhui at Huazhong University of Science and Technology reported a cationic polymer artificial SEI film with high ion transference number, which can effectively improve the stable cycling performance of lithium-lithium batteries in carbonate electrolyte systems (1 mA cm⁻¹). -2 However, the low ionic conductivity and unavoidable solvent corrosion of this artificial SEI film limit its further application. (Adv. Mater. 2021, 33, 2007 428) The Li Hong research group at the Institute of Physics, Chinese Academy of Sciences, reported a photocurable polymer artificial SEI film that isolates the electrolyte from direct contact with metallic lithium, avoiding solvent corrosion of the lithium anode and effectively protecting the metallic lithium anode. A lithium-lithium symmetric battery was stably cycled for 700 h (0.5 mA cm⁻¹) in a carbonate electrolyte system. -2 1mA h cm -2(Nano Energy 95(2022)106983) However, the low ionic conductivity and ion transference number of this artificial SEI membrane result in poor cycle stability of the battery at high rates, which still limits its further application. The research groups of Zhang Qiang from Tsinghua University and Huang Jiaqi from Beijing Institute of Technology reported an organic-inorganic composite artificial SEI membrane, which is a high ion transference number artificial SEI membrane prepared from LLZTO inorganic particles and lithium-modified perfluorosulfonic acid resin. Li+ =0.82). Directly coating this composite protective layer onto the surface of the lithium metal electrode can effectively suppress the formation of lithium dendrites, but it also results in a low room-temperature ionic conductivity (3.0 × 10⁻⁶). -5 S cm -1 This significantly reduces its application in lithium metal batteries at room temperature. (Adv. Mater. 2019, 1808392) Therefore, there is an urgent need to provide an artificial SEI film material for lithium metal anodes that can be widely used in lithium secondary batteries, possessing both high ionic conductivity and high ion transference number, capable of isolating solvents and stabilizing the lithium ion stripping / deposition process, inhibiting the growth of lithium metal dendrites, thereby improving the safety and cycle performance of lithium metal batteries. Summary of the Invention

[0004] In view of this, the present invention provides a bipolar artificial SEI film for lithium metal anodes, which combines high ionic conductivity and high ion transference number, and provides a method for preparing the artificial SEI film and a method for preparing a lithium metal battery. The method is simple, uses readily available raw materials, is safe and pollution-free, and is suitable for large-scale mass production.

[0005] The second objective of this invention is to provide a method for preparing a bipolar artificial SEI film for lithium metal anodes; the method is simple to prepare, the raw materials are readily available and safe and pollution-free, and it is suitable for large-scale mass production.

[0006] The third objective of this invention is to provide a lithium metal battery, wherein the artificial SEI film of the lithium metal battery is a lithium metal anode bipolar artificial SEI film as described in this invention.

[0007] To achieve the objectives of this invention, the following technical solutions are provided.

[0008] A bipolar artificial SEI film for lithium metal anodes is prepared by mixing carbonate, polar polymer, polymer prepolymer, photoinitiator and salt in the dark, directly coating the mixture onto the surface of lithium metal, and then curing it directly under ultraviolet light in a protective atmosphere; the protective gas is an inert gas or nitrogen.

[0009] The carbonate is one or more of the following: ethylene carbonate, fluoroethylene carbonate, trifluoropropylene carbonate, difluoroethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, dipropyl carbonate, diphenyl carbonate, butene carbonate, dibutyl carbonate, tetrabutanol dicarbonate, glyceryl carbonate difluoroacetate, glyceryl carbonate alcohol trifluoroacetate, and glyceryl carbonate alcohol ethanesulfonate.

[0010] The polar polymer is one or more of polyacrylonitrile, polyvinyl alcohol, poly(N-cyanomethacrylamide), and polyvinyl alcohol-β-cyanoethyl ether.

[0011] The lithium salt is one or more of lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(fluorosulfonyl)amine, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium bis(oxalato)borate, lithium di(oxalato)borate, lithium tetrafluoroborate, lithium phosphate, and lithium difluorophosphate.

[0012] The polymer prepolymer is one or more selected from polyethylene glycol diacrylate, butyl acrylate, polyethylene glycol methyl ether methacrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropene triglycidyl ether, N,N-dimethylbisacrylamide, and N-cyanomethacrylamide. Preferably, the number average molecular weight of the polymer prepolymer is 100 to 1000.

[0013] The photoinitiator is one or more of 2-hydroxy-2-methylphenylacetone, 2,2-dimethoxy-2-phenylacetophenone, benzophenone peroxide, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone is commercially available, for example, Irgacure 2529 manufactured by Ciba Specialty Chemicals; bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide is commercially available, for example, Irgacure 819 manufactured by Ciba Specialty Chemicals.

[0014] The preferred mass ratio of polar polymer, carbonate solvent, lithium salt, polymer prepolymer, and photoinitiator is 1–10:20–75:1–15:5–25:0.01–0.5.

[0015] A method for preparing a lithium metal anode bipolar artificial SEI film according to the present invention, the method steps are as follows:

[0016] (1) In a temperature range of 20 to 55°C and in a dry inert atmosphere, the artificial SEI film prepolymer solvent is mixed evenly with 1 to 10 wt% polar polymer, 20 to 75 wt% carbonate solvent, 1 to 15 wt% lithium salt, 5 to 25 wt% polymer prepolymer and 0.01 to 0.5 wt% photoinitiator by mass percentage; (2) Under the protection of protective gas and in a near-anhydrous and oxygen-free environment, the mixture obtained in step (1) is directly coated onto the surface of the lithium metal anode with a scraper; the coating thickness of the mixture is 0.1 μm to 10 μm; after curing by ultraviolet light irradiation, a bipolar artificial SEI film for lithium metal anodes as described in this invention is obtained.

[0017] The protective gas is an inert gas or nitrogen with a purity of 99% or higher.

[0018] The preferred coating thickness of the mixture is 0.1 μm to 10 μm.

[0019] The wavelength of the ultraviolet lamp is preferably 365nm to 400nm.

[0020] Curing is preferably achieved by irradiating with ultraviolet light for 1 to 5 minutes.

[0021] Beneficial effects

[0022] 1. This invention provides a bipolar artificial SEI film for lithium metal anodes. The electrolyte uses a polar polymer as a component, and the ionic conductivity is enhanced through a carbonate solvent and lithium salt. Lithium ion desolvation is promoted through ion-dipole interactions between polar cyano (-C≡N) functional groups and anions, and hydrogen bonding interactions between alcohol hydroxyl functional groups and carbonate solvent molecules, thereby improving lithium ion migration and isolating free carbonate molecules from contact with the lithium anode. The introduction of polymer prepolymers and photoinitiators, through interactions between functional groups and lithium metal, participates in and promotes the formation of a polymer-derived SEI film organic layer on the lithium metal surface, allowing the artificial SEI film to adhere tightly to the lithium metal anode surface, forming a stable lithium metal anode-artificial SEI film interface.

[0023] 2. This invention provides a bipolar artificial SEI film for lithium metal anodes. The bipolar artificial SEI film has both high ionic conductivity and high ion transference number, effectively preventing corrosion by free carbonate solvents, stabilizing the stripping / deposition process of lithium metal, inhibiting the growth of lithium dendrites caused by lithium ion concentration polarization, and exhibiting low overpotential and long-term cycle stability during constant current polarization, which can significantly improve the electrochemical performance and safety of lithium metal batteries.

[0024] 3. This invention provides a method for preparing a bipolar artificial SEI film for lithium metal anodes. The preparation process of the method is simple, uses conventional equipment, the raw materials are readily available, and it is safe and pollution-free. It does not require the use of organic solvents such as N,N-dimethylformamide (DMF) or acetonitrile, and is suitable for large-scale mass production. Attached Figure Description

[0025] Figure 1 This is a scanning electron microscope image of a lithium metal anode bipolar artificial SEI film prepared in Example 1.

[0026] Figure 2 This is an ion mobility diagram of a lithium metal anode bipolar artificial SEI film prepared in Example 1.

[0027] Figure 3 For lithium-lithium symmetric batteries using a bipolar artificial SEI film for a lithium metal anode prepared in Example 1,

[0028] 5mA / cm 2 Constant current plating / stripping diagram with current density. Detailed Implementation

[0029] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are for the convenience of those skilled in the art to understand the present invention and are not intended to limit the scope of protection of the present invention. Improvements made by those skilled in the art without departing from the basic concept of the present invention should fall within the scope of protection of the present invention.

[0030] In the following embodiments:

[0031] All argon gases used have a purity of 99% or higher.

[0032] The polar polymer network gel electrolyte prepared in the following examples was tested as follows:

[0033] (1) The morphology of the bipolar artificial SEI membrane was observed using a scanning electron microscope.

[0034] Test instrument: Hitachi S4800

[0035] (2) The test system was assembled into a bipolar artificial SEI membrane@lithium metal│electrolyte│bipolar artificial SEI membrane@lithium metal symmetric cell by using AC impedance-steady-state current combined measurement to determine the ion transport number of the bipolar artificial SEI membrane. Linear voltammetry was used on a CHI660E electrochemical workstation, with the impedance measurement frequency range being 0.1Hz to 10Hz. 5 Hz; the polarization voltage tested is 10mV.

[0036] Testing instrument: CHI660E electrochemical workstation, Shanghai Chenhua

[0037] (3) Electrochemical performance testing

[0038] Assembly of lithium symmetric batteries: In a glove box filled with argon gas of ≥99% purity, the bipolar artificial SEI membrane@lithium metal, separator, electrolyte, and bipolar artificial SEI membrane@lithium metal are sequentially placed into a 2025 button cell casing. Then, the two cell casings are pressed and fastened together using a presser to obtain a lithium-lithium symmetric battery. After the assembled lithium battery is left to stand at 30°C for 48 hours, its electrochemical performance is tested.

[0039] The deposition / stripping of lithium metal and sodium was tested using the LAND battery testing system. The constant current density was 5 mA / cm², and the deposition surface capacity was 1 mAh / cm².

[0040] Test instrument: LAND battery test system, model CT2001A, Wuhan Jinno Electronics Co., Ltd.

[0041] Example 1:

[0042] The lithium anode bipolar artificial SEI membrane provided in this embodiment comprises 5 wt% polyvinyl alcohol-β-cyanoethyl ether, 55 wt% ethylene carbonate, 15 wt% lithium bis(trifluorosulfonyl)imide, 25 wt% polyethylene glycol diacrylate (Mn=400) and 0.02 wt% 2-hydroxy-2-methylphenylacetone.

[0043] The preparation method is as follows: In a glove box filled with argon, where H2O is less than 0.1 ppm and O2 is less than 0.1 ppm, at a temperature of 55°C, 15 wt% lithium bis(trifluorosulfonyl)imide, 5 wt% polyvinyl alcohol-β-cyanoethyl ether, 25 wt% polyethylene glycol diacrylate (Mn = 400), and 0.02 wt% 2-hydroxy-2-methylphenylacetone are added sequentially to 55 wt% ethylene carbonate. During the addition process, the mixture is stirred thoroughly to ensure uniform mixing. The mixture is then directly coated onto the surface of a lithium metal anode using a scraper. The coating thickness is 5.0 μm. The UV lamp wavelength is 365 nm to 400 nm, and the film is photocured for 5 minutes to obtain the bipolar artificial SEI film.

[0044] The polar polymer network gel electrolyte prepared in this embodiment was tested as follows:

[0045] (1) The morphology of the lithium anode bipolar artificial SEI film was observed using scanning electron microscopy.

[0046] The thickness of the lithium anode bipolar artificial SEI film is 3.7 μm.

[0047] (2) The ion transference number of the lithium anode bipolar artificial SEI film was measured using an AC impedance-steady-state current coupled test: the ion transference number of the lithium anode bipolar artificial SEI film was 0.86. Figure 2 As shown.

[0048] (3) Electrochemical performance testing

[0049] Test results: Lithium-lithium symmetric batteries at 10mA / cm 2 Current density and 2mAh / cm 2 At the surface capacity, it can cycle stably for 300 hours without any short circuits. Figure 3 As shown.

[0050] Example 2:

[0051] The lithium anode bipolar artificial SEI film provided in this embodiment includes 7 wt% of polyvinyl alcohol-β-cyanoethyl ether and polyvinyl alcohol composite, 60 wt% fluoroethylene carbonate, 10 wt% lithium dioxaborate, 23 wt% polyethylene glycol diacrylate (Mn=400) and 0.02 wt% photoinitiator.

[0052] The preparation method is as follows: In a glove box filled with argon, where H2O is less than 0.1 ppm and O2 is less than 0.1 ppm, at a temperature of 55°C, 10 wt% lithium dioxalate borate, 7 wt% polyvinyl alcohol-β-cyanoethyl ether and polyvinyl alcohol complex, 23 wt% polyethylene glycol diacrylate (Mn = 500) and 0.02 wt% photoinitiator are added sequentially to 60 wt% fluoroethylene carbonate. During the addition process, the mixture is stirred thoroughly to ensure uniform mixing. The mixture is then directly coated onto the surface of the lithium metal anode using a scraper. The coating thickness is 3.0 μm. The mixture is photocured under UV light at a wavelength of 365 nm to 400 nm for 5 min to 15 min to obtain the artificial SEI film for the lithium metal battery.

[0053] The polar polymer network gel electrolyte prepared in this embodiment was tested as follows:

[0054] (1) The morphology of the lithium anode bipolar artificial SEI film was observed using scanning electron microscopy.

[0055] The thickness of the lithium anode bipolar artificial SEI film is 1.8 μm.

[0056] (2) The ion transference number of the lithium anode bipolar artificial SEI film was measured using AC impedance-steady-state current combined test: the ion transference number of the lithium anode bipolar artificial SEI film was 0.89.

[0057] (3) Electrochemical performance testing

[0058] Test results: Lithium-lithium symmetric batteries at 10mA / cm 2 Current density and 2mAh / cm 2 At the surface capacity, it can cycle stably for 500 hours without any short circuits.

[0059] Example 3:

[0060] The lithium anode bipolar artificial SEI film provided in this embodiment comprises 1 wt% polyacrylonitrile and polyvinyl alcohol composite, 75 wt% methyl ethyl carbonate, 5 wt% lithium hexafluorophosphate, 19 wt% polyethylene glycol diacrylate and 0.02 wt% 2,2-dimethoxy-2-phenylacetophenone.

[0061] The preparation method is as follows: In a glove box filled with argon, where H2O is less than 0.1 ppm and O2 is less than 0.1 ppm, at a temperature of 55°C, 5 wt% lithium hexafluorophosphate, 1 wt% polyacrylonitrile and polyvinyl alcohol composite, 19 wt% polyethylene glycol diacrylate and 0.02 wt% 2,2-dimethoxy-2-phenylacetophenone are added sequentially to a 75 wt% carbonate solvent. During the addition process, the mixture is stirred thoroughly to ensure uniform mixing. The mixture is then directly coated onto the surface of a lithium metal anode using a scraper. The coating thickness is 7.0 μm. The mixture is then photocured under ultraviolet light at a wavelength of 365 nm to 400 nm for 5 min to 15 min to obtain the artificial SEI film for the lithium metal battery.

[0062] The polar polymer network gel electrolyte prepared in this embodiment was tested as follows:

[0063] (1) The morphology of the lithium anode bipolar artificial SEI film was observed using scanning electron microscopy.

[0064] The thickness of the lithium anode bipolar artificial SEI film is 5.1 μm.

[0065] (2) The ion transference number of the lithium anode bipolar artificial SEI film was measured using AC impedance-steady-state current combined test: the ion transference number of the lithium anode bipolar artificial SEI film was 0.66.

[0066] (3) Electrochemical performance testing

[0067] Test results: Lithium-lithium symmetric batteries at 10mA / cm 2 Current density and 2mAh / cm 2 At the surface capacity, it can cycle stably for 300 hours without any short circuits.

[0068] Example 4:

[0069] The lithium anode bipolar artificial SEI film provided in this embodiment comprises 5 wt% polyvinyl alcohol-β-cyanoethyl ether, 70 wt% fluoroethylene carbonate, 15 wt% lithium bis(trifluorosulfonyl)imide, 10 wt% polymer prepolymer and 0.02 wt% photoinitiator.

[0070] The preparation method is as follows: In a glove box filled with argon, where H2O is less than 0.1 ppm and O2 is less than 0.1 ppm, at a temperature of 50°C, 15 wt% lithium difluorophosphate, 5 wt% polar polymer, 10 wt% polymer prepolymer, and 0.02% photoinitiator are added sequentially to 70 wt% fluoroethylene carbonate. During the addition process, the mixture is stirred thoroughly to ensure uniform mixing. The mixture is then directly coated onto the surface of the lithium metal anode using a scraper. The coating thickness is 10 μm. The UV lamp wavelength is 365 nm to 400 nm, and the mixture is photocured for 5 to 15 minutes to obtain the artificial SEI film for the lithium metal battery.

[0071] The polar polymer network gel electrolyte prepared in this embodiment was tested as follows:

[0072] (1) The morphology of the lithium anode bipolar artificial SEI film was observed using scanning electron microscopy.

[0073] The thickness of the lithium anode bipolar artificial SEI film is 8.3 μm.

[0074] (2) The ion transference number of the lithium anode bipolar artificial SEI film was measured using AC impedance-steady-state current combined test: the ion transference number of the lithium anode bipolar artificial SEI film was 0.78.

[0075] (3) Electrochemical performance testing

[0076] Test results: Lithium-lithium symmetric batteries at 10mA / cm 2 Current density and 2mAh / cm 2 At the surface capacity, it can cycle stably for 360 hours without any short circuits.

[0077] Example 5:

[0078] The lithium anode bipolar artificial SEI film provided in this embodiment includes 10 wt% poly(N-cyanomethacrylamide) and polyvinyl alcohol composite, 55 wt% ethylene carbonate, 10 wt% lithium bis(fluorosulfonyl)amine, 25 wt% polymer prepolymer and 0.02 wt% photoinitiator (2-hydroxy-2-methylphenylacetone).

[0079] The preparation method is as follows: In a glove box filled with argon, where H2O is less than 0.1 ppm and O2 is less than 0.1 ppm, at a temperature of 50°C, 10 wt% lithium bis(fluorosulfonyl)amine, 10 wt% poly(N-cyanomethacrylamide) and polyvinyl alcohol composite, 25 wt% polymer prepolymer, and 0.05 wt% 2-hydroxy-2-methylphenylacetone are added sequentially to 55 wt% ethylene carbonate. During the addition process, the mixture is stirred thoroughly to ensure uniform mixing. The mixture is then directly coated onto the surface of the lithium metal anode using a scraper. The coating thickness is 1 μm. The mixture is then photocured under UV light at a wavelength of 365 nm to 400 nm for 5 min to 15 min to obtain the artificial SEI film for the lithium metal battery.

[0080] The polar polymer network gel electrolyte prepared in this embodiment was tested as follows:

[0081] (1) The morphology of the lithium anode bipolar artificial SEI film was observed using scanning electron microscopy.

[0082] The thickness of the lithium anode bipolar artificial SEI film is 0.3 μm.

[0083] (2) The ion transference number of the lithium anode bipolar artificial SEI film was measured using AC impedance-steady-state current combined test: the ion transference number of the lithium anode bipolar artificial SEI film was 0.83.

[0084] (3) Electrochemical performance testing

[0085] Test results: Lithium-lithium symmetric batteries at 10mA / cm 2 Current density and 2mAh / cm 2 At the surface capacity, it can cycle stably for 300 hours without any short circuits.

Claims

1. A bipolar artificial SEI film for lithium metal anodes, characterized in that, The artificial SEI film comprises the following components: polar polymer, carbonate solvent, lithium salt, polymer prepolymer, and photoinitiator; The mass ratio of polar polymer, carbonate solvent, lithium salt, polymer prepolymer and photoinitiator is 1-10:20-75:1-15:5-25:0.01-0.

5. The polar polymer is selected from polyvinyl alcohol. β Cyanide ether, polyvinyl alcohol and polyvinyl alcohol β Cyanobyl ether complex, polyvinyl alcohol and polyacrylonitrile complex, polyvinyl alcohol and poly(N) cyanomethacrylamide complex; The polymer prepolymer is selected from polyethylene glycol diacrylate and / or polyethylene glycol methyl ether methacrylate.

2. The lithium metal anode bipolar artificial SEI film according to claim 1, characterized in that, The carbonate solvent is selected from at least one of ethylene carbonate, fluoroethylene carbonate, trifluoropropylene carbonate, difluoroethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, dipropyl carbonate, diphenyl carbonate, butene carbonate, dibutyl carbonate, tetrabutanol dicarbonate, glyceryl carbonate alcohol difluoroacetate, glyceryl carbonate alcohol trifluoroacetate, and glyceryl carbonate alcohol ethanesulfonate.

3. The lithium metal anode bipolar artificial SEI film according to claim 1, characterized in that, The lithium salt is selected from at least one of lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(fluorosulfonyl)amine, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium bis(oxalato)borate, lithium di(oxalato)borate, lithium tetrafluoroborate, lithium phosphate, and lithium difluorophosphate.

4. The lithium metal anode bipolar artificial SEI film according to claim 1, characterized in that... The photoinitiator is selected from 2 hydroxyl 2 Methyl acetone, 2,2 Dimethoxy 2 Phenylacetone, Benzophenone Peroxide, 2 hydroxyl 2 methyl 1 [4 (2 [hydroxyethoxy)phenyl] 1 Acetone and bis(2,4,6) trimethylbenzoyl) At least one of phenylphosphine oxide.

5. A method for preparing a lithium metal anode bipolar artificial SEI film according to any one of claims 1-4, characterized in that, The method includes: (1) uniformly mixing a polar polymer, a carbonate solvent, a lithium salt, a polymer prepolymer and a photoinitiator in a dry, inert atmosphere at a temperature range of 20°C to 50°C; (2) The mixture obtained in step (1) is directly coated onto the surface of the lithium metal anode with a scraper; and cured by ultraviolet light to obtain a bipolar artificial SEI film of lithium metal anode.

6. The method for preparing a bipolar artificial SEI film for lithium metal anodes according to claim 5, characterized in that: The coating thickness of the mixture is 0.1 μm to 10 μm; the wavelength of the ultraviolet lamp is 365 nm to 400 nm, and the artificial SEI film of the lithium metal battery is obtained by photocuring for 1 min to 5 min.

7. A lithium metal battery, characterized in that: The lithium metal battery comprises a lithium metal negative electrode, an artificial SEI film, an electrolyte, a separator, and a positive electrode, wherein the artificial SEI film is as described in claim 1.

4. The lithium metal anode bipolar artificial SEI film according to any one of the claims.

Citation Information

Patent Citations

  • Binder for separator of non-aqueous electrolyte battery comprising 2-cyanoethyl group-containing polymer and separator and battery using the same

    CN102738425A

  • Negative electrode for lithium metal battery and lithium metal battery including the same

    US20160380314A1